Relationships between communication satisfaction dimensions and organizational identification - Mustafa Kamal, Daniel Kamal (2014)
Organizational identification has been shown to be related to a myriad of favorable outcomes for the organization, including intention to remain with the organization, organizational citizenship behavior, and willingness to act in the best interests of the organization. This has led to the notion that organizational identification is an effective tool in improving organizational outcome and effectiveness. However, there is still a scarcity of research supporting purely organizational communication factors as antecedents of organizational identification. The study was conducted to determine the relationships between communication satisfaction dimensions and organizational identification among the academic staff of a public university. Specifically, the study aimed to determine the relationship between communication satisfaction as a singular construct and organizational identification as well as the relationships between the individual dimensions of communication satisfaction and organizational identification. The study also examined the differences in organizational identification according to selected demographic factors namely organizational tenure, organizational position, and gender. Lastly, the study also aimed to determine the dimensions of communication satisfaction that acted as significant predictors of organizational identification. Social Identity Theory was used to guide the present study. The study utilized a quantitative approach to the phenomenon and employed the use of a survey method. Random stratified sampling was used and a sample size of 299 respondents consisting of academic staff was obtained. Data was collected using two established instruments, the Downs and Hazen’s Communication Satisfaction Questionnaire (CSQ) and the Mael’s Scale for Organizational Identification (MOI). The data obtained was analyzed using both descriptive and inferential statistics, including the use of t-test and ANOVA. The results showed that there was a positive and significant relationship between communication satisfaction and organizational identification. However, it was a weak correlation, thus indicating that communication satisfaction had a low impact on organizational identification. The study also showed that organizational identification differed according to organizational tenure and organizational position, with organizational members having been with the organization longer or having higher positions in the organizational hierarchy exhibiting higher levels of organizational identification. No differences were shown between genders. Among the dimensions of Communication Satisfaction, only the Personal Feedback dimension and Media Quality dimension were found to be significant predictors of organizational identification. The findings suggest that communication satisfaction does not greatly impact organizational identification in the context of academicians at a public university. However, earlier research that suggests organizational identification is influenced by organizational tenure and organizational position was substantiated and holds true in the present context.